2015
DOI: 10.1161/circheartfailure.114.001734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Estimated Plasma Volume Reduction on Renal Function for Acute Heart Failure Differs Between Patients With Preserved and Reduced Ejection Fraction

Abstract: Background-The prognostic relevance of plasma volume reduction (PVR) in acute heart failure patients remains unclear because of the confounding hemodynamic effect of left ventricular ejection fraction impairment on kidney function. Methods and Results-Subjects enrolled in the West Tokyo Heart Failure Registry were examined. The PV at admission and discharge was estimated from the subjects' body weight and its deviation from the ideal body weight. Patients in the top tertile of estimated PVR were classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
(44 reference statements)
1
41
0
Order By: Relevance
“…16 Furthermore, a previous report showed that, unlike furosemide, tolvaptan results in fluid loss without adversely affecting renal hemodynamics. 18 Given that renal function in ADHF patients with HFpEF is thought to be especially sensitive to a reduction in renal perfusion, 10 it is tempting to speculate that the efficacy of tolvaptan therapy on the prevention of WRF might be higher in ADHF patients …”
Section: Treatment Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…16 Furthermore, a previous report showed that, unlike furosemide, tolvaptan results in fluid loss without adversely affecting renal hemodynamics. 18 Given that renal function in ADHF patients with HFpEF is thought to be especially sensitive to a reduction in renal perfusion, 10 it is tempting to speculate that the efficacy of tolvaptan therapy on the prevention of WRF might be higher in ADHF patients …”
Section: Treatment Protocolmentioning
confidence: 99%
“…18 In addition, a recent study has shown that aggressive fluid removal by diuretic therapy causes WRF, especially in ADHF patients with HFpEF compared with those with HFrEF. 10 Presumably, this is related to a susceptibility to a reduction in renal blood flow in ADHF patients with HFpEF. 10 Therefore, we decided to elucidate the therapeutic effect of tolvaptan on WRF in ADHF patients with HFpEF.…”
Section: Study Limitationsmentioning
confidence: 99%
See 3 more Smart Citations